The quantity of zinc absorbed from wheat in adult women Is enhanced by biofortification - Rosada, Jorge L.; Hambidge, K. Michael; Miller, Leland V.; Garcia Olga P.; Westcott, Jamie; Gonzalez, Karla; Conde, Jennifer; Hotz, Christine; Pfeiffer, Wolfgang; Ortiz-Monasterio, Ivan; Krebs, Nancy F. (International Food Policy Research Institute, 2009)
Biofortification of staple food crops with micronutrients could reduce micronutrient malnutrition at relatively low cost. Zinc is especially important in this consideration as a lack of dietary zinc is a major cause of early childhood morbidity and mortality. Indicators of zinc deficiency and quantitative data on the negative effects of phytates on zinc absorption are also limited. Measurements of zinc bioavailability and the effect of phytates on these, as addressed in this paper, are thus of extra significance.